Developing the Data for Nuclear Waste Disposal - Investigations of the Lac du Bonnet Batholith - Tammemagi, H. (Geoscience Canada, 1979)
Summary Atomic Energy of Canada Limited (AECL) in conjunction with other federal agencies, universities and commercial firms has undertaken a program to demonstrate that the burial of nuclear wastes deep into carefully selected geological formations is a viable and safe method of disposal. During the next three years, approximiately eight formations m the Canadian Shield, representing various classes of plutons, will be investigated in detail. This paper describes a case history of the investigation of one of these, the Lac du Bonnet batholith, Manitoba.